1995
DOI: 10.1002/eji.1830251114
|View full text |Cite
|
Sign up to set email alerts
|

Naive CD4+ T cells confer idiotype‐specific tumor resistance in the absence of antibodies

Abstract: CD4+ T cells can recognize a processed idiotypic peptide derived from the mouse lambda 2(315) immunoglobulin light chain. The idiotypic peptide is presented on the I-E(d) class II major histocompatibility complex molecule. Mice made transgenic for a lambda 2(315)-specific alpha beta T cell receptor have been demonstrated to be specifically resistant against a tumor challenge with the MOPC315 (alpha,lambda 2(315)) plasmacytoma (Lauritzsen, G. F., Weiss, S., Dembic, Z. and Bogen, B., Proc. Natl. Acad. Sci. USA 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
97
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 77 publications
(102 citation statements)
references
References 29 publications
5
97
0
Order By: Relevance
“…16,26 Bogen et al 26 reported that id-specific CD4 ϩ T cells can protect against challenges with small numbers of the MOPC315 plasmocytoma. On the other hand, Ö sterborg et al 27 detected both CD4 ϩ and CD8 ϩ idiotype T cell reactivity in early stage myeloma patients following id-protein vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…16,26 Bogen et al 26 reported that id-specific CD4 ϩ T cells can protect against challenges with small numbers of the MOPC315 plasmocytoma. On the other hand, Ö sterborg et al 27 detected both CD4 ϩ and CD8 ϩ idiotype T cell reactivity in early stage myeloma patients following id-protein vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…Mice BALB/cABom, C.B-17/lcrBom, C57BL/6JBom, C3H/HeJBom, SCID on C.B-17 background, and the 2 315 -specific TCR-transgenic mice on a C.B-17-SCID background (15) were all from M&B (Ry, Denmark). The 2 315 -specific TCR-transgenic mice on BALB/c background (16) and the 2 315 -specific TCR-transgenic mice on a Rag2 Ϫ/Ϫ BALB/c background (unpublished) were bred in our animal facility.…”
Section: Methodsmentioning
confidence: 99%
“…[9][10][11][12]17 In spite of the fact that the vast majority of myelomas failed to express MHC class II molecules, CD4 + T cells may play an important role in tumour immunity. Qin and Blankenstein 31 recently showed that cellular immunity against MHC class II negative tumours can be mediated by CD4 + T cells through an IFN-␥-dependent mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…These findings could be confirmed in several other B cell tumour models. [7][8][9] In most of these studies, anti-Id immunity was dependent on T cells rather than on anti-Id antibodies. Bogen et al have shown that Id-specific CD4 + T cells are essential for tumour protection in the MOPC myeloma model.…”
mentioning
confidence: 99%
See 1 more Smart Citation